Algebra Word Problems Viewed from Self-Regulated Learning - Al Hawari, Defahayu As Syaura; Ibrahim, Ibrahim; Mistima Maat, Siti (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2024)
The ability of junior high school students to solve algebra word problems in learning mathematics is an important part and must be mastered well.  However, the results of observations carried out by researcher at one of the junior high schools in Yogyakarta showed that students had difficulty solving and understanding algebra word  problems. In addition, when working on assignments given by the teacher, students tend to rely on the results of their friends' work without showing the initiative to learn independently. Therefore, this research aims to analyze students' difficulties in solving algebra word problems in terms of their self-directed learning. This research is a descriptive qualitative research with the research subjects being all class VII students in one of the junior high schools in Yogyakarta. The data collection techniques in this research used a self-directed learning scale and a learning difficulties test. The research results show that students with high self-directed learning are able to solve problems in algebra word problems, but are less careful in obtaining the final results. Students in the  middle self-regulated learning category are experiencing difficulties in writing descriptions and simplifying and operating algebraic multiplication and division operations. Meanwhile, students with low self-regulated learning have difficulty understanding the concept of algebraic operations and applying it in the context of algebraic word problems. It is hoped that the research findings will provide an idea for teachers to train students' self-regulated learning so that their ability to solve algebra word problems can be even better.